The global burden of stomach cancer and its risk factors from 1990 to 2021: findings from the Global Burden of Disease Study 2021 - Le Zhou; Bo Han; Yinjiao Yuan; Zhuowei Dong; Yijing Shi; Ruinian Zheng (BMC Public Health)
Abstract Background: Stomach cancer is one of the leading cancers worldwide. This article aims to analyze and assess the global burden of stomach cancer from 1990 to 2021, identify its main risk factors, and make projections for 2030 using the newly published 2021GBD database. Methods: In the Global Burden of Disease Study 2021, we analyzed the incidence, death, and DALYs related to stomach cancer. Age-standardized incidence rate (ASIR), age-standardized death rate (ASDR), and age-standardized DALYs rate were obtained and analyzed. Results: The incidence of stomach cancer increased from 980,899 in 1990 to 1,230,233 in 2021. ASIR has declined from 24.76 to 14.33 per 100,000 people. ASDR dropped from 22.01 to 11.20 per 100,000 people. The global DALYs for stomach cancer was 22,786,633, and the age-standardized DALYs rate was 262.75 per 100,000 people. Men have higher rates of ASDR, ASIR, and age-standardized DALYs compared to women. In 2021, East Asia have the highest burden of stomach cancer associated with behavioral, high-sodium diets, smoking, and dietary habits. Projections for 2030 indicate that ASIR, ASDR, and age-standardized DALYs rates will all continue to decline. Conclusion: This study found that although the ASIR and ASDR of stomach cancer have significantly declined, the absolute number of cases has continued to rise due to the continuous growth and aging of the population. In high SDI (socio-demographic index) regions, such as Western Europe and North America, the burden of stomach cancer has decreased. The high burden in low SDI regions needs to be alleviated through targeted interventions such as smoking control and improvement of dietary habits.